Effects of water table level on soil CO2 respiration in West Kalimantan forested and bare peatland: An experimental stage - DWI ASTIANI; BURHANUDDIN BURHANUDDIN; MUHAMMAD TAHERDJADEH; LISA M. CURRAN (Smujo International, 2016)
Abstract. Astiani D, Burhanuddin, Taherdjadeh M, Curran LM. 2016. Effects of water table level on soil CO2 respiration in West Kalimantan forested and bare peatland: An experimental stage. Nusantara Bioscience 8: 201-206. Peatland forest is one of ecosystems that are susceptible to the alterations of water regimes. Our previous study demonstrated that hydrologic conditions are predominant variables in determining carbon respiration rates from peat soils. However, we have limited empirical measures of how hydrologic conditions (i.e., soil water table) affect the carbon respirations. A study had been conducted to ascertain the effects of water table levels on soil CO2 respirations of West Kalimantan coastal forested and bare peatland. We simulated natural intact peat core condition by designing 25 of